Insights into Wall-Jet Scouring Characterization with the Kinect Device: Benefits and Limitations - Hadi Bali; Seyed Hossein Mohajeri; Amir Samadi (Advances in Civil Engineering)
This study explores the use of the Kinect device for measuring Three-Dimensional (3D) Digital Elevation Models (DEMs) of wall-jet scour holes and its benefits and limitations. The Kinect device can accurately measure wall-jet scour holes in dry conditions with an accuracy of ±0.05 cm, but significant errors occur in the presence of water due to water surface refraction. A code based on Snell’s law was developed to correct these errors, resulting in good agreement with point gauge measurements with an accuracy of ±0.12 cm. The method is not recommended for tail-water depth ratios smaller than three and densimetric Froude numbers larger than 7.75 due to water surface fluctuations. The findings have important implications for improving the efficiency and accuracy of scour hole measurements in hydraulic engineering, particularly for submerged wall-jet scouring, and the developed code can also be applied to other optical measurement devices.